2016
DOI: 10.1093/jee/tow094
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transfer of Spinosad inCoptotermes formosanus(Isoptera: Rhinotermitidae)

Abstract: Slow-acting and nonrepellent termiticides are possible candidates for nestmate to nestmate transfer called horizontal transfer. For the horizontal transfer study of spinosad, Coptotermes formosanus Shiraki was released in sand and soil at 1, 25, and 50 ppm Entrust(®) for 1 h and then mixed with healthy untreated termites for 21 d at the ratio of 1:1. Donor and recipient termites began to contact and groom each other immediately after release. Mortality of termites was recorded at 1, 3, 7, and 14 d after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This process directly or indirectly influences individual and social interactions among colony members. Insecticides that possess the ability of horizontal transfer, which is a significant mode of action, have been utilized to facilitate this function in social insects through the behavior of replacing the corpses of colony members [ 68 , 69 ]. A study reported that red imported fire ants, being a social insect, were found to be unaffected by the presence of corpses treated with any of the test chemicals, indicating that they were not deterred from removing them from the nest area [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process directly or indirectly influences individual and social interactions among colony members. Insecticides that possess the ability of horizontal transfer, which is a significant mode of action, have been utilized to facilitate this function in social insects through the behavior of replacing the corpses of colony members [ 68 , 69 ]. A study reported that red imported fire ants, being a social insect, were found to be unaffected by the presence of corpses treated with any of the test chemicals, indicating that they were not deterred from removing them from the nest area [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal transfer of insecticides is an important mode of action to control social pests. [35][36][37] Untreated ants may acquire a lethal dose of toxicants when carrying and moving the corpses killed by certain insecticides. 13,38,39 For example, Wiltz et al 13 reported that corpses killed by the fast-acting insecticide bifenthrin caused higher horizontal toxicity against recipient ants than slower-acting insecticides such as chlorfenapyr, fipronil, and thiamethoxam.…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal transfer of insecticides is an important mode of action to control social pests 35–37 . Untreated ants may acquire a lethal dose of toxicants when carrying and moving the corpses killed by certain insecticides 13,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal transfer of chemical pesticides is a mode of action that requires a limited amount of pesticides, which can be transferred from pesticide-exposed (treated) individuals to unexposed (untreated) individuals. This method has been widely applied to control the gregarious insects such as termites [18,19], ants [20,21], and bed bugs [22]. Here we hypothesized that the chemical pesticide (i.e., avermectin) can be horizontally transferred within the aggregations of H. vitessoides larvae, and avermectin-transfer bioassays were conducted to verify this under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%